The Effect Of Training And Work Involvement On Performance With Motivation As An Intervening Variable At The Fire And Rescue Service Of Medan City - Vandi Saputra; Rosita Rosita; Fenny Krisna Marpaung; Betty Betty; Suriati Tirawani (CV. Aksara Global Akademia, 2024)
The population is increasing every year and in line with the increasing number of dwellings in the city of Medan, the Fire and Rescue Service is needed to provide services in terms of creating peace and public order in the fire sub affairs so that the city government needs to pay special attention in improving equipment, facilities and infrastructure that support employees in order to carry out their duties properly. In terms of using the equipment and all facilities provided by the organization to work, employees must first be trained so that skills, knowledge and work attitudes are formed so that employees are able to make maximum use of all facilities. Organizational leaders who have been able to create a work atmosphere where employees' needs are met, considered and their development is supported will increase work involvement, especially employees of the Medan City Fire and Rescue Service in providing services to the community. Employees who are trained and have a high sense of work engagement will consistently show good performance with the support of motivation from the organization such as incentives and policies that facilitate employees in carrying out their duties. Leaders also need to consistently provide direction to members in achieving performance goals because employees will be better able to carry out tasks and challenges in their work. Research conducted in clarifying the influence between training and work involvement on performance through motivation with quantitative methods shows the study findings that training and work involvement have a positive effect on motivation, training and work involvement have a positive effect on performance. Motivation as an intervening variable between training and work engagement on performance has a positive effect. Meanwhile, training and work engagement have no simultaneous influence on motivation.